Spectral efficient hybrid wireless optical broadband access network - Ali Mohammed Shaddad, Redhwan Qasem (2013)
Spectral efficient hybrid Wireless Optical Broadband Access Network (WOBAN) is a favourable architecture for next generation access network. It is an optimal combination of an optical backhaul and a wireless front-end for an efficient access network. This thesis proposes the WOBAN in two architecture designs: the WOBAN based on transmission of wireless signal as a BaseBand signal Over Fiber (BBOF), and the spectral efficient hybrid WOBAN based on transmission of wireless Multi-Input Multi-Output Orthogonal Frequency Division Multiplexing (MIMO OFDM) signals over Wavelength Division Multiplexing Passive Optical Network (WDM PON) as a Radio Over Fiber (ROF). Wireless MIMO signals which have the same carrier frequency cannot propagate over a single optical fiber on the same wavelength, so a novel Optical Single-SideBand Frequency-Translation (OSSBFT) technique is proposed to solve this problem in the second WOBAN architecture. The OSSB-FT technique is an efficient method since it excludes the crosstalk between different broadband wireless MIMO signals with the same carrier Radio Frequency (RF). Besides, it is a cost-effective technique as one optical source is enough to generate the optical carrier which is reused at the Access Point (AP), and multiple wavelengths for carrying several wireless MIMO signals over the same fiber. The physical layer performance is reported in both architecture designs of the WOBAN. In the first design, theWOBAN provides data rate of 2 Gb/s bidirectional optical backhaul for each wavelength channel along 20 km optical fiber link. In the wireless front-end, each Optical Network Unit/Access Point (ONU/AP) propagates data rate of 54 Mb/s along 50 m wireless link. The spectral efficient hybrid WOBAN achieved a data rate of 7.80 Gb/s along the optical backhaul of 20 km. The wireless front-end AP could support data rate up to 240 Mb/s along 100 m outdoor wireless link.